ANALISIS HUBUNGAN PENGGUNAAN MEDIA MANIPULATIF DENGAN HASIL BELAJAR MATEMATIKA SISWA BERDASARKAN NILAI MID - Indira Putri Saskia; Al Ikhfa Hassurad; Sulistiawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning outcomes of mathematics students in elementary school and the importance of using learning media that can help students understand mathematical concepts concretely. This study aims to determine the relationship between the use of manipulative media and students' mathematics learning outcomes based on MID scores at UPT SDN 18 Binamu. The research uses a quantitative approach with a type of correlational research. The research population was 15 students in grade VI with a sampling technique using total sampling. Data collection was carried out through a questionnaire using manipulative media and documentation of students' mathematics MID scores. The research instrument is tested for validity and reliability before use. Data analysis was carried out using the JASP application through descriptive statistical analysis, Shapiro-Wilk normality test, and Pearson Product Moment correlation test. The results showed that the data was normally distributed with a significance value of 0.109 (p > 0.05). The results of the Pearson correlation test showed a correlation coefficient value of r = 0.952 with a significance value of p < 0.001. These results show that there is a very strong and significant positive relationship between the use of manipulative media and students' mathematics learning outcomes. The use of manipulative media helps students understand abstract mathematical concepts to become more concrete so that students are more active and easily understand the learning material. Thus, manipulative media can be used as an alternative learning medium to improve mathematics learning outcomes of elementary school students.